Majelis Selawat as a Political Communication Medium in Indonesia - Zulhazmi, Abraham Zakky; Bakti, Andi M. Faisal (Kalijaga Journal of Communication, 2024)
This study attempts to analyze the propaganda delivered by the Habib in PKB Bersholawat initiated by PKB’s Majelis Pesona. After the reformation, Majelis Selawat in Indonesia was utilized for various interests, including for conveying political messages. One of them was Partai Kebangkitan Bangsa (PKB) through the Majelis Pesona. Majelis Selawat in Indonesia became an effective medium for gathering large masses. Religion and politics touch the emotional and personal side of the congregation. Majelis Selawat are popular among Nahdliyin and Indonesian Muslims in general. PKB Bersholawat contains messages of da'wah and politics. PKB utilizes the Majelis Selawat as a medium of political communication to bring in the masses. PKB utilizes religious figures such as Habibs, Kiai, and Gus to achieve specific goals. With a qualitative approach and Jacques Ellul's propaganda theory, this study concludes that PKB utilizes the Majelis Selawat to convey political messages. The Majelis Selawat were chosen because they can bring in large numbers of Muslim masses and reflect PKB's identity as a party born from the aspirations of Nahdlatul Ulama members, with the jargon of the rahmatan lil alamin party. The propaganda used by PKB in PKB Bersholawat is a bandwagon, transfer, and glittering generalities, in the form of support for Muhaimin Iskandar to become president, which is conveyed through prayers read by a Habib.